1993
DOI: 10.22358/jafs/69881/1993
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substituting milfoil, St. Johnswort and lovage for antibiotics on chicken performance and meat quality

Abstract: One thousand one-day-old broiler chicks were divided into 5 experimental groups: the control groups received an antibiotic in their feed, the remaining groups-3% dried milfoil (Achillea millefolium L.) and St. Johnswort (Hypericum perforatum L.) herbage and lovage roots (Levisticum officinale Koch) mixed in various proportions. Body weight gain and feed utilization over a 9-week period of the experiment were similar in the experimental and control groups. A beneficial effect of milfoil on body weight gain of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Meat colours, taste and smell were all improved when broiler 329 chickens were fed on diets with XTRACT®, containing capsaicin, carvacrol and 330 cinnamaldehyde (Jamroz et al, 2003). Dietary yarrow herb supplements fed either singly or 331 in combination with St. John's wort have enhanced organoleptic perception in broiler chicken 332 meat (Fritz et al, 1993…”
Section: Effect Of Phytochemicals On Intestinal Microflora Populationmentioning
confidence: 99%
“…Meat colours, taste and smell were all improved when broiler 329 chickens were fed on diets with XTRACT®, containing capsaicin, carvacrol and 330 cinnamaldehyde (Jamroz et al, 2003). Dietary yarrow herb supplements fed either singly or 331 in combination with St. John's wort have enhanced organoleptic perception in broiler chicken 332 meat (Fritz et al, 1993…”
Section: Effect Of Phytochemicals On Intestinal Microflora Populationmentioning
confidence: 99%
“…Wilman & Derrick (1994) found 1.94% and Kirchner (1955) more than 2% N in dandelion at similar harvest dates in Aberystwyth and Hohenheim, respectively. Crude protein contents of 11% have been reported for yarrow (Fritz et al, 1993). These data suggest that the forbs themselves suffered nitrogen deficiency.…”
Section: Discussionmentioning
confidence: 78%
“…The natural materials as alternative growth promoters such as medicinal plants are widely accepted (Noland 1965 andAboul-Fotouh et al, 1999). Also, some studies indicated that such plants have favorable effects on live weight gain and feed efficiency with broiler chicken (Fritz et al, 1992 andFritz et al, 1993) and with cows (Singh and Taparia, 1992).…”
Section: Introductionmentioning
confidence: 99%